2022
DOI: 10.1177/20552076221139090
|View full text |Cite
|
Sign up to set email alerts
|

Screen media and non-screen media habits among preschool children in Singapore, South Korea, Japan, and Finland: Insights from an unsupervised clustering approach

Abstract: The main purpose of the research was to describe the daily screen media habits and non-screen media habits like indoor and outdoor play, and sleep of preschool children aged 2 to 6 years from Singapore, South Korea, Japan, and Finland using a content-validated online questionnaire (SMALLQ®) and unsupervised cluster analysis. Unsupervised cluster analysis on 5809 parent-reported weekday and weekend screen and non-screen media habits of preschool children from the four countries resulted in seven emergent cluste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…Our findings align with studies conducted in other countries using the SDQ to measure the socio-emotional development of preschool children, which have reported an association between increased ST and externalising behavioural problems such as hyperactivity, emotional symptoms, conduct issues, and poor prosocial behaviour [52][53][54]. With the advancement of media technology and increased accessibility, high ST among children in Asia has been highlighted as a significant concern [55]. Our study's results revealed a favourable association between externalising behaviour problems in children when all three recommended activity guidelines were met.…”
Section: Discussionsupporting
confidence: 89%
“…Our findings align with studies conducted in other countries using the SDQ to measure the socio-emotional development of preschool children, which have reported an association between increased ST and externalising behavioural problems such as hyperactivity, emotional symptoms, conduct issues, and poor prosocial behaviour [52][53][54]. With the advancement of media technology and increased accessibility, high ST among children in Asia has been highlighted as a significant concern [55]. Our study's results revealed a favourable association between externalising behaviour problems in children when all three recommended activity guidelines were met.…”
Section: Discussionsupporting
confidence: 89%
“…A recent study that examined preschool children's screen time across four countries (Singapore, South Korea, Japan, and Finland) found that parents from different cultures had different views of screen use (entertainment, education, etc.) and that children and parents spent diverse time on screen and non‐screen activities (Chia et al., 2022). For example, Japanese parents predominantly perceived screen as a mean of entertainment, spent less time in parent–child activities, and, like their children, spent less time on non‐screen activities (Chia, et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…and that children and parents spent diverse time on screen and non‐screen activities (Chia et al., 2022). For example, Japanese parents predominantly perceived screen as a mean of entertainment, spent less time in parent–child activities, and, like their children, spent less time on non‐screen activities (Chia, et al., 2022). Thus, further research on the intersectional effects of ethnicity, culture, and SES is needed to better understand early screen use.…”
Section: Discussionmentioning
confidence: 99%
“…Sementara itu, untuk anak dibawah usia 2 tahun belum diperbolehkan untuk menggunakan gadget. Namun hasil penelitian menunjukan bahwa banyak anak usia dini yang menggunakan gadget melebihi batas yang disarankan terutama dari negara berkembang (Chia et al, 2022). Padahal apabila penggunaan gadget secara berlebihan ini terus berlanjut akan banyak dampak negatif yang muncul pada anak.…”
Section: Latar Belakangunclassified
“…Screen media and non-screen media habits among preschool children in Singapore, South Korea, Japan, and Finland: Insights from an unsupervised clustering approach Chia et al (2022) Singapura, Korea Selatan, Jepang, dan Finlandia. 5809 orang tua yang memiliki anak berusia 2 -6 tahun.…”
Section: Hartshorne Et Al (2021)mentioning
confidence: 99%